Situation of oncological patients during COVID-19 pandemic with particular emphasis on lung cancer patients - Michalina Pytka; Paweł Oszczędłowski; Justyna Nowaczek; Aleksandra Żywicka (Kazimierz Wielki University, 2021)
Introduction and purpose: The purpose of this study is to review literature about alterations to treatment regimens to lung cancer during COVID-19 pandemic accessible on PubMed platform. In pulmonary neoplasms, early diagnosis and treatment is a key to ensure patient safety. Burdening of healthcare systems during pandemic has resulted in many obstacles in oncologic treatment. A brief description of the state of knowledge:  The lung cancer is the most frequent and the most deadly cancer in men and women. COVID-19 is a pulmonary infectious disease whose spread around the world has resulted in a pandemic. At the onset of the worldwide pandemic, many institutions, including healthcare facilities were closed, making it more difficult to provide oncological patients the treatment compliant with the standards. The anxiety of patients caused by the pandemic has caused delays in treatment that can cause progression of the disease. In patients with lung cancer mortality of COVID-19 was around 50%, which made their visits at hospital hazardous. Before the accessibility of anti-COVID-19 vaccines telemedical healthcare was one of the ways to provide healthcare to oncological patients. Conclusions: Patients with lung cancer are one of the risk groups of COVID-19. Delays in their treatment caused by the pandemic are potentially dangerous and negatively affect the therapy. Telemedicine is a useful too provide medical care, but has its own limitations.